Estrogen Acts Through Estrogen Receptor 2b to Regulate Hepatobiliary Fate During Vertebrate Development. Issue 5 (6th November 2020) - Chaturantabut, Saireudee; Shwartz, Arkadi; Garnaas, Maija K.; LaBella, Kyle; Li, Chia‐Cheng; Carroll, Kelli J.; Cutting, Claire C.; Budrow, Nadine; Palaria, Amrita; Gorelick, Daniel A.; Tremblay, Kimberly D.; North, Trista E.; et al.
Abstract : Background and Aims: During liver development, bipotent progenitor cells differentiate into hepatocytes and biliary epithelial cells to ensure a functional liver required to maintain organismal homeostasis. The developmental cues controlling the differentiation of committed progenitors into these cell types, however, are incompletely understood. Here, we discover an essential role for estrogenic regulation in vertebrate liver development to affect hepatobiliary fate decisions. Approach and Results: Exposure of zebrafish embryos to 17β‐estradiol (E2) during liver development significantly decreased hepatocyte‐specific gene expression, liver size, and hepatocyte number. In contrast, pharmacological blockade of estrogen synthesis or nuclear estrogen receptor (ESR) signaling enhanced liver size and hepatocyte marker expression. Transgenic reporter fish demonstrated nuclear ESR activity in the developing liver. Chemical inhibition and morpholino knockdown of nuclear estrogen receptor 2 b ( esr2b ) increased hepatocyte gene expression and blocked the effects of E2 exposure. esr2b −/− mutant zebrafish exhibited significantly increased expression of hepatocyte markers with no impact on liver progenitors, other endodermal lineages, or vasculature. Significantly, E2‐stimulated Esr2b activity promoted biliary epithelial differentiation at the expense of hepatocyte fate, whereas loss of esr2b impaired biliary lineage commitment. Chemical and genetic epistasis studies identified bone morphogenetic protein (BMP) signaling as a mediator of the estrogen effects. The divergent impact of estrogen on hepatobiliary fate was confirmed in a human hepatoblast cell line, indicating the relevance of this pathway for human liver development. Conclusions: Our studies identify E2, esr2b, and downstream BMP activity as important regulators of hepatobiliary fate decisions during vertebrate liver development. These results have significant clinical implications for liver development in infants exposed to abnormal estrogen levels or estrogenic compounds during pregnancy.